Generating test data from state-based specifications - Offutt, Jeff; Liu, Shaoying; Abdurazik, Aynur; Ammann, Paul (Software testing, verification & reliability, 2003)
Although the majority of software testing in industry is conducted at the system level, most formal research has focused on the unit level. As a result, most system‐level testing techniques are only described informally. This paper presents formal testing criteria for system level testing that are based on formal specifications of the software. Software testing can only be formalized and quantified when a solid basis for test generation can be defined. Formal specifications represent a significant opportunity for testing because they precisely describe what functions the software is supposed to provide in a form that can be automatically manipulated. This paper presents general criteria for generating test inputs from state‐based specifications. The criteria include techniques for generating tests at several levels of ion for specifications (transition predicates, transitions, pairs of transitions and sequences of transitions). These techniques provide coverage criteria that are based on the specifications and are made up of several parts, including test prefixes that contain inputs necessary to put the software into the appropriate state for the test values. The test generation process includes several steps for transforming specifications to tests. These criteria have been applied to a case study to compare their ability to detect seeded faults. Copyright © 2003 John Wiley & Sons, Ltd.